ANALISIS TINGKAT JANGKAUAN PELAYANAN PENGEMBANGAN MINIMARKET DI KORIDOR JALAN TERHADAP PERILAKU KONSUMEN STUDI KASUS KORIDOR JL. SEMARANG-BOJA KECAMATAN MIJEN - Meika Deby Priyanka; Eppy Yuliani (Universitas Islam Sultan Agung Semarang, 2017)
Minimarket is one form of retail trade continues to grow and spread rapidly in the neighborhoods and the corners of the big cities in Indonesia as well as business becomes the most expansive retail trade in Indonesia. Semarang as the capital of Central Java is also facing the phenomenon. One of the mini-environments where scattered settlements and significantly expand the District Mijen. Since the first minimarket outlets operating in the region in 2007 until February 2013 there have been 7 minimarket outlets operating. Research Question It can be concluded from this study is what the development of a minimarket in District Mijen can influence changes in consumer behavior in determining the location of shopping options? The research methode used in this study using a quantitative deductive rationalistic. Based on questionnaire, interviews and observations, the identification and analysis techniques of quantitative descriptive analysis and interpretation of cross-tabulation analysis techniques among variables that were examined in the form of table analysis and chi-square crosstab. The development of minimarket condition every day visitors who come around 300 people, with the total 7 minimarket mini market until 2013. Minimarket well as projected needs 10 years from now seen that the projected need for services in the District Mijen minimarket stated is sufficient to serve. Consumer behavior is largely based on the mini frequency of visits was done 2 times a week, daily necessities, distance and outlets are clean and organized is the biggest factor affecting the motivation of respondents to shop at the mini. Range of minimarket located in District Mijen is overlapped between the mini with the other minimarket. Distance range that is divided into the ring I 500 meters and ring II 1 Km. The need for evaluation of spatial planning through distribution pattern minimarket and community shopping destination location so as to anticipate the entry of modern retail in maintaining continuity of traditional retail (traditional retailers). Keywords: minimarket, consumer behavior, and the range of services